Role of Ultrasonography in the Era of 3 Tesla MRCP: A Comparative Study in Obstructive Jaundice. - Patil, Vikram; Das, Sudha Kiran; Devkant, Dr; Hiremath, Rudresh; Shetty, Sachin; Raj, Vinay (Asian Journal of Medical Radiological Research, 2019)
Background: Biliary obstruction is caused by various diseases. In a suspected case of biliary obstruction with clinical and laboratory findings suggestive of obstructive jaundice, the main aim of radiologist is to confirm the presence of obstruction identify its location, extent and probable cause. 3D MRCP virtually demonstrates anatomy of the biliary and pancreatic ducts in 3 Tesla MRI system. Ultrasonography still remains the first imaging modality for obstructive jaundice. The aim of the study was to evaluate the diagnostic efficacy of USG vs. MRCP with 3 Tesla MRI in patients of obstructive jaundice. Subjects and Methods: After institutional ethical committee approval, 90 patients confirmed to have features of obstructive jaundice referred for Ultrasonography and MRCP and subsequently underwent ERCP / Surgery were evaluated. It was a Prospective correlational study. Inclusion Criteria were patients with clinical diagnosis of obstructive jaundice referred for Ultrasonography and MRCP and subsequently underwent ERCP / Surgery. Exclusion Criteria were patients non compatible for MRI and other modalities (ERCP), Patients in whom histological diagnosis was not available, Patients unwilling for MRCP / ERCP / Surgery. Results: Accuracy of ultrasound was 75 % and MRCP 98 % in detection and delineation of obstructive biliary pathologies. Sensitivity, specificity and accuracy for choledocholithiasis is 80%, 100% & 80% respectively for Ultrasonography and 100% for MRCP. The Sensitivity and Specificity for Ultrasonography was 71% and 100% in detection of biliary obstruction secondary to biliary strictures and for MRCP, the sensitivity and specificity was 100%. Sensitivity and specificity for malignant pathologies in this study was 73 % and 100% respectively on Ultrasonography, while that on MRCP was 93.3% and 100% respectively. Conclusion: Ultrasonography as a screening modality is useful to confirm or exclude biliary dilatation and to choose patients for MRCP examination. MRCP is an important non-invasive imaging investigation in the pre-operative evaluation of patients with obstructive jaundice. Magnetic resonance (MR) cholangiopancreatography, combines the advantages of projectional imaging with those of cross-sectional imaging, is an established diagnostic technique. Technical advances over the past decade, including the refinement of 3.0-T imaging capabilities, have added to the usefulness of this noninvasive method. Though MRCP can be considered as the gold standard for diagnostic non-invasive evaluation of the pancreaticobiliary system in cases of obstructive jaundice, ultrasound will always remain the first choice.